Emergence of a KPC Variant Conferring Resistance to Ceftazidime-Avibactam in a Widespread ST11 Carbapenem-Resistant Klebsiella pneumoniae Clone in China - Li, Xi; Quan, Jingjing; Ke, Huanhuan; Wu, Wenhao; Feng, Yu; Yu, Yunsong; Jiang, Yan (Frontiers in Microbiology, 2021)
Abstract Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection poses a great threat to public health worldwide, and KPC-2-producing strains are the main factors responsible for resistance to carbapenems in China. Ceftazidime/avibactam (CZA) is a novel β-lactam/β-lactamase inhibitor combination with good activity against KPC-2 carbapenemase and is becoming the most important option for treating KPC-producing CRKP infection. Here, we report the emergence of a novel KPC-2 variant, designated KPC-74, produced by K. pneumoniae strain KP55, that conferred CZA resistance in a patient after CZA exposure. The novel blaKPC-74 variant showed a deletion of 6 nucleotides at positions 712-717 compared with blaKPC-2, and this deletion resulted in the consequent deletion of glycine and valine at positions 239 and 240. Antimicrobial susceptibility testing showed that KP55 presents multidrug resistance, including resistance to CZA and ertapenem, but is susceptible to imipenem, meropenem and colistin. The blaKPC-74 gene was located on a plasmid, as determined by S1-nuclease pulsed-field gel electrophoresis followed by southern blotting, and confirmed to be 133,766 bp in length by whole-genome sequencing on both the Illumina and MinION platforms. The CZA resistance phenotype of the novel KPC variant was confirmed by both transformation of the blaKPC-74-harbouring plasmid and a blaKPC-74 gene cloning assay, showing a 64-fold higher CZA minimum inhibitory concentration (MIC) than the recipient strains. The G239_V240del observed in KPC-74 was outside the omega-loop region but was still close to the active site Ser70 and omega-loop in the protein tertiary structure. The enzyme kinetic parameters and IC50 values further indicated that the hydrolytic activity of the KPC-74 enzyme against ceftazidime was potentiated twofold and that the affinity between KPC-74 and avibactam was alleviated 17-fold compared with that of the KPC-2 allele. This CZA resistance mediated by KPC-74 could be selected after CZA therapy and evolved to be more diverse and heterogeneous. Surveillance of CZA resistance is urgently needed in clinical settings.